Концептуальні засади організаційно-економічного забезпечення інклюзивного розвитку сільських територій - Філюк, Дмитро Олександрович; Шматковська, Тетяна Олександрівна (My University, 2024)
У статті досліджено проблему забезпечення інклюзивного розвитку сільських територій, яка набуває все більшого значення у контексті сучасних викликів соціально-економічного розвитку. Розглянуто концептуальні засади організаційно-економічного забезпечення даного процесу. Проаналізовано стратегії та методи, спря-мовані на забезпечення інклюзії всіх верств суспільства у розвиток сільських територій, з урахуванням їх-ніх особливостей та потреб. Визначено ключові аспекти інклюзивного розвитку, такі як підвищення якості життя, соціальна справедливість, економічна стійкість та збалансоване використання природних ресурсів сільських територій. Досліджено механізми формування та реалізації політик, спрямованих на формування сприятливого середовища для інклюзивного розвитку сільських територій. Визначено, що для досягнення інклюзивного розвитку сільських територій необхідно враховувати комплексний підхід, який охоплює різно-манітні аспекти функціонування соціо-еколого-економічних систем, такі як економічний розвиток, соціальна інтеграція, доступ до освіти та медичних послуг, формування нових робочих місць та підтримка місцевих під-приємницьких ініціатив
The article examines the problem of ensuring the inclusive development of rural areas, which is gaining more and more importance in the context of modern challenges of socio-economic development. The conceptual foundations of the organizational and economic support of this process are considered. Strategies and methods aimed at ensuring the inclusion of all layers of society in the development of rural areas, taking into account their characteristics and needs, were analyzed. The key aspects of inclusive development are identified, such as improving the quality of life, social justice, economic sustainability and balanced use of natural resources in rural areas. The mechanisms of formation and implementation of policies aimed at creating a favorable environment for the inclusive development of rural areas have been studied. It was determined that in order to achieve the inclusive development of rural areas, it is necessary to take into account a comprehensive approach that covers various aspects of the functioning of socio-ecological and economic systems, such as economic development, social integration, access to education and medical services, the creation of new jobs and support for local entrepreneurial initiatives . It has been investigated that the key elements of the successful implementation of the conceptual principles of inclusive development are the functional cooperation of all interested parties, the inclusion of the public in decision-making processes regarding the development of regional socio-economic projects, as well as ensuring the effective use of resources and the introduction of innovative approaches to managing the development of rural areas. The need to take regional and local specifics into account when planning and implementing the conceptual principles of inclusive development has been determined, since each rural area has its own unique characteristics that can affect the capabilities and needs of its residents.
Keywords: інклюзивний розвиток; сталий розвиток; сільські території; концепція розвитку; інклюзія; inclusive development; sustainable development; rural areas; development concept; inclusion; 338.244.47